Differences in the Selvester QRS score after primary PCI strategy and conservative treatment for STEMI patients with negative T waves. Issue 6 (1st August 2019) - Kalinauskiene, Egle; Gerviene, Dalia; Bacharova, Ljuba; Krivosikova, Zora; Naudziunas, Albinas
Abstract: Background: According to current guidelines, the main indications for PCI in patients with STEMI are ST‐segment deviations and defined time from the onset of symptoms. Negative T wave at admission can be a sign of prolonged ischemia or spontaneous reperfusion. In both situations, the urgent intervention is questionable. We evaluated the infarct size and in‐hospital mortality in STEMI patients with negative T wave in cases of primary PCI strategy compared with conservative treatment. Methods: A retrospective analysis of 116 STEMI patients with negative T wave at the presenting ECG was performed. Sixty‐eight patients (59%) underwent primary PCI strategy (PCI group), and 48 (41%) were treated conservatively (non‐PCI group). The infarct size estimated by using the Selvester score, and in‐hospital mortality were evaluated. Results: The difference between Selvester score values at admission and at discharge in the non‐PCI group was statistically significant (1.48; 95% CI 0.694–2.27), while no significant difference was observed in the PCI group (−0.07; 95% CI −0.546–0.686). The in‐hospital mortality was higher in the non‐PCI group; however, the numbers were relatively small: PCI 2 (2.9%) and non‐PCI 5 (10.4%). Conclusion: In this study, we showed a reduction in the infarct size estimated by Selvester score in STEMI patients with negative T wave who were treated conservatively, while there was no significant change in the infarct size after primary PCI strategy. The higher mortality in patients treated conservatively could be attributed to higher age and comorbidities in the non‐PCI group. It seems that conservative treatment strategy might be an option in STEMI patients with negative T wave.